Systems Biology Analysis of Temporal In vivo Brucella melitensis and Bovine Transcriptomes Predicts host:Pathogen Protein–Protein Interactions - Rossetti, Carlos A.; Drake, Kenneth L.; Lawhon, Sara D.; Nunes, Jairo S.; Gull, Tamara; Khare, Sangeeta; Adams, Leslie G. (Frontiers in Microbiology, 2017)
To date, fewer than 200 gene-products have been identified as Brucella virulence factors, and most were characterized individually without considering how they are temporally and coordinately expressed or secreted during the infection process. Here, we describe and analyze the in vivo temporal transcriptional profile of Brucella melitensis during the initial 4 h interaction with cattle. Pathway analysis revealed an activation of the “Two component system” providing evidence that the in vivo Brucella sense and actively regulate their metabolism through the transition to an intracellular lifestyle. Contrarily, other Brucella pathways involved in virulence such as “ABC transporters” and “T4SS system” were repressed suggesting a silencing strategy to avoid stimulation of the host innate immune response very early in the infection process. Also, three flagellum-encoded loci (BMEII0150-0168, BMEII1080-1089, and BMEII1105-1114), the “flagellar assembly” pathway and the cell components “bacterial-type flagellum hook” and “bacterial-type flagellum” were repressed in the tissue-associated B. melitensis, while RopE1 sigma factor, a flagellar repressor, was activated throughout the experiment. These results support the idea that Brucella employ a stealthy strategy at the onset of the infection of susceptible hosts. Further, through systems-level in silico host:pathogen protein–protein interactions simulation and correlation of pathogen gene expression with the host gene perturbations, we identified unanticipated interactions such as VirB11::MAPK8IP1; BtaE::NFKBIA, and 22 kDa OMP precursor::BAD and MAP2K3. These findings are suggestive of new virulence factors and mechanisms responsible for Brucella evasion of the host's protective immune response and the capability to maintain a dormant state. The predicted protein–protein interactions and the points of disruption provide novel insights that will stimulate advanced hypothesis-driven approaches toward revealing a clearer understanding of new virulence factors and mechanisms influencing the pathogenesis of brucellosis.